Growth performance of Macrobrachium rosenbergii in nursery phase with varying levels of n3:n6 fatty acids - Leela, G; Ramanathan, N; Francis, T (Indian Journal of Fisheries, 2011)
A total of fifteen experimental diets with diverse lipid levels, n6 and n3 fractions and n6: n3 ratios were formulated and compared with a lipid control basal diet. The feeding trials were carried out in the post-larvae of Macrobrachium rosenbergii for a period of 35 days. Among the seven experimental diets formulated with constant n3 (0.33% of n3 fatty acids in the diet), a wider n6: n3 ratio (18:75:1) and high lipid (9.1%) diet performed well. There was a systematic reduction in growth performance as the n6: n3 ratio was narrowed down (from18.75 towards 1:1). This indicates that apart from n3 fatty acids composition, other factors such as n6: n3 ratio, n6 and lipid levels also play a significant role in the growth performance of M. rosenbergii during nursery phase. Blending ofsaturated fatty acids rich coconut oil with cod liver oil even at a minimum level (10% coconut oil +90% cod liver oil) improved the status of prawn feed considerably. The experimental feed meant for nursery rearing of M. rosenbergii with 2% lipid, n6: n3 ratio of 18:1 and with 0.062% n3 content in the diet performed extremly well, in terms of biogrowth parameters.